Microalgae biodiesel: A systematic review in Iran. (October 2021) - Ravanipour, Masoumeh; Hamidi, Ali; Mahvi, Amir Hossein
Abstract: The use of fossil fuels has faced the world with new challenges, so that renewable energy has become a part of the world's total energy consumption. Iran is rich in natural energy resources and can consider for using the renewable fuels like biofuels as an alternative to non-renewable. This study has two purposes. First, it purposes to provide an overview on all studies conducted in Iran in the field of biodiesel production from microalgae and fish waste. Second, it purposes to study the biodiesel production potential from those two sources in Bushehr province. Overall, 109 peer-reviewed articles were retrieved, of which 15 original articles were included. The results of the systematic review showed that biodiesel production research from algae and fish waste in Iran has increased in the last ten years. In addition, the minimum and maximum algae lipid content was obtained equal 17.5 and 52%, respectively. The lowest and highest amount of oil productivity was obtained equal 0.026 and 0.154 g/l.day, respectively. Also, the biodiesel production potential of Bushehr from aquatic algae and fish waste was estimated at about 196.1 kt, which is equal to 19.25% of the total diesel fuel requirements of Bushehr and 1.2% of the total diesel consumption of Iran in transportation sector. In general, the total revenue of $ 118.8 million from the aquatic microalgae and fish waste of Bushehr province can be obtained. The study concludes with biodiesel production policy concepts and avenues for future researches. Graphical abstract: Image 1 Highlights: The minimum and maximum algae lipid content was obtained equal 17.5 and 52%, respectively. The lowest and highest amount of oil productivity was obtained 0.026 and 0.154 g/l.day, respectively. About 177.1 and 19 kt of biodiesel can be produced from microalgae and fish waste in Bushehr province. A total income of 118.8 million dollar from microalgae and fish waste can be achieved in Bushehr province.